1977
DOI: 10.1007/bf01918819
|View full text |Cite
|
Sign up to set email alerts
|

A cholinergic modulator

Abstract: Soluble proteins obtained from presynaptic cholinergic vesicles have been tested regarding their effects to modify postsynaptic spike generation. The results suggest that these proteins (or derivatives, incl. glycopeptides) may act as modulators in increasing the effectiveness and duration of postsynaptic spike generation. They may partake in generation of homosynaptic (posttetanic) potentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1984
1984

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Earlier, Hamilton in his studies of the effect of diazepam (Hamilton 1967) and flurazepam (Hamilton & Stone 1982) on the in-vitro rat phrenic nerve-hemidiaphragm preparation, also observed this biphasic effect. The mechanism underlying this biphasic pattern of the concentration-response curve is still unclear, but Torda & Gage (1977) and Torda & Murphy (1979) showed that diazepam not only reduced the duration of the end-plate currents and hence the amplitude of the postsynaptic potentials in the mouse hemidiaphragm, but also acts presynaptically where it increases the quantal content of the end-plate potential in the mouse sternomastoid nerve muscle preparation. Torda and his colleagues suggested that this increase in quantal content is likely to mask some of the postsynaptic depression of the amplitude of the end-plate potential by diazepam.…”
Section: Benzodiazepines and Muscle Relaxationmentioning
confidence: 99%
“…Earlier, Hamilton in his studies of the effect of diazepam (Hamilton 1967) and flurazepam (Hamilton & Stone 1982) on the in-vitro rat phrenic nerve-hemidiaphragm preparation, also observed this biphasic effect. The mechanism underlying this biphasic pattern of the concentration-response curve is still unclear, but Torda & Gage (1977) and Torda & Murphy (1979) showed that diazepam not only reduced the duration of the end-plate currents and hence the amplitude of the postsynaptic potentials in the mouse hemidiaphragm, but also acts presynaptically where it increases the quantal content of the end-plate potential in the mouse sternomastoid nerve muscle preparation. Torda and his colleagues suggested that this increase in quantal content is likely to mask some of the postsynaptic depression of the amplitude of the end-plate potential by diazepam.…”
Section: Benzodiazepines and Muscle Relaxationmentioning
confidence: 99%